Polyoxovanadates as new P‐glycoprotein inhibitors: insights into the mechanism of inhibition. Issue 3 (30th December 2021) - Kita, Diogo Henrique; de Andrade, Gisele Alves; Missina, Juliana Morais; Postal, Kahoana; Boell, Viktor Kalbermatter; Santana, Francielli Sousa; Zattoni, Ingrid Fatima; Zanzarini, Isadora da Silva; Moure, Vivian Rotuno; Rego, Fabiane Gomes de Moraes; Picheth, Geraldo; de Souza, Emanuel Maltempi; et al.
Abstract : A promising strategy to overcome multidrug resistance is the use of inhibitors of ABC drug transporters. For this reason, we evaluated the polyoxovanadates (POVs) [V10 O28 ] 6– (V10 ), [H6 V14 O38 (PO4 )] 5− (V14 ), [V15 O36 Cl] 6− (V15 ) and [V18 O42 I] 7− (V18 ) as inhibitors of three major multidrug resistance‐linked ABC transporters: P‐glycoprotein (P‐gp), ABCG2 and MRP1. All of the POVs selectively inhibited P‐gp. V10 and V18 were the two most promising compounds, with IC50 values of transport inhibition of 25.4 and 22.7 µm, respectively. Both compounds inhibited P‐gp ATPase activity, with the same IC50 value of 1.26 µm . V10 and V18 triggered different conformational changes in the P‐gp protein with time‐dependent inhibition, which was confirmed using the synthesized salt of V10 with rhodamine B, RhoB‐V10 . The hydrophilic nature of POVs supports the hypothesis that these compounds target an unusual ligand‐binding site, opening new possibilities in the development of potent modulators of ABC transporters. Abstract : One of the main challenges in cancer treatment is the resistance mediated by P‐glycoprotein (P‐gp). We described polyoxovanadates (POVs) as new selective P‐gp inhibitors. The two best compounds were [V10 O28 ] 6– (V10 ) and [V18 O42 (I)] 7− (V18 ). These compounds were not transported, inhibited the ATPase activity and triggered different protein conformational changes. In addition, compound RhoB‐V10 confirmed the time‐dependent intracellular accumulation of POVs.